Altered Serum Thyrotropin Concentrations in Dogs with Primary Hypoadrenocorticism before and during Treatment. (11th October 2017) - Reusch, C.E.; Fracassi, F.; Sieber‐Ruckstuhl, N.S.; Burkhardt, W.A.; Hofer‐Inteeworn, N.; Schuppisser, C.; Stirn, M.; Hofmann‐Lehmann, R.; Boretti, F.S.
Abstract : Background: Thyrotropin (TSH) can be increased in humans with primary hypoadrenocorticism (HA) before glucocorticoid treatment. Increase in TSH is a typical finding of primary hypothyroidism and both diseases can occur concurrently (Schmidt's syndrome); therefore, care must be taken in assessing thyroid function in untreated human patients with HA. Objective: Evaluate whether alterations in cTSH can be observed in dogs with HA in absence of primary hypothyroidism. Animals: Thirty dogs with newly diagnosed HA, and 30 dogs in which HA was suspected but excluded based on a normal ACTH stimulation test (controls) were prospectively enrolled. Methods: cTSH and T4 concentrations were determined in all dogs and at selected time points during treatment (prednisolone, fludrocortisone, or DOCP) in dogs with HA. Results: cTSH concentrations ranged from 0.01 to 2.6 ng/mL (median 0.29) and were increased in 11/30 dogs with HA; values in controls were all within the reference interval (range: 0.01–0.2 ng/dL; median 0.06). There was no difference in T4 between dogs with increased cTSH (T4 range 1.0‐2.1; median 1.3 μg/dL) compared to those with normal cTSH (T4 range 0.5‐3.4, median 1.4 μg/dL; P =0.69) and controls (T4 range 0.3‐3.8, median 1.8 μg/dL; P =0.35). After starting treatment, cTSH normalized after 2–4 weeks in 9 dogs and after 3 and 4 months in 2 without thyroxine supplementation. Conclusions and Clinical Relevance: Evaluation of thyroid function in untreated dogs with HA can lead to misdiagnosis of hypothyroidism; treatment with glucocorticoids for up to 4 months can be necessary to normalize cTSH.